Pseudotumor inflamatorio por Fasciola hepática: a propósito de un caso - Tume Jara, Lucía (2015)
ntroduction: Fasciola hepatica is a parasite of the class Trematoda. It commonly has been found in developing countries. When it infects humans is characterized by a triad of fever, pain in right upper quadrant and peripheral eosinophilia. We present a 67-year-old female from a rural town of the north of Lima, Peru, it was found abdominal pain, eosinophilia and focal hepatic lesions. For this reason, a hepatic mass was the initial suspicion. The hepatic biopsy was performed and one of the findings was eosinophilia. Fasciola hepatica infection should be considered as part of differential diagnosis in hepatic tumors with eosinophilia when the origin of the patient is from endemic areas of F. hepatica.